2020
DOI: 10.31234/osf.io/pbg2v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Don't slap the fish: The relationship between dietary Omega-3 intake and physical aggression is mediated by motor inhibition in response to distressed faces

Abstract: The innate violence inhibition mechanism (VIM) purportedly regulates maladaptive aggressive behavior through motor inhibition, in response to expressions of distress, and is implicated in psychopathy-related aggression. Deficiency in eicosapentaenoic acid (EPA; an omega-3 fatty acid) is implicated in aggression and callous-unemotional (CU) traits, however, its relationship to the VIM remains unknown. Two studies tested relationships between EPA intake, personality (aggression, CU traits), and electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The example of COVID-19 showed that, factors in the physical environment (infection) can affect people's endurance and ability to focus (i.e., temperament traits) when people contracted COVID and increases anxiety after that (i.e., induces psychopathology), and there is not much that cultural factors can do about it [72]. Physical factors regulating CBPs depicted in Figure 2A can also include the amount of sunlight as it determines the release of hypothalamic orexins and so behavioural arousal [23], diets ( [43][44][45]) and the use of common psychostimulants (alcohol, tobacco) .…”
Section: Jingle-jangle Fallacies Related To Concepts Of "Environments"mentioning
confidence: 99%
“…The example of COVID-19 showed that, factors in the physical environment (infection) can affect people's endurance and ability to focus (i.e., temperament traits) when people contracted COVID and increases anxiety after that (i.e., induces psychopathology), and there is not much that cultural factors can do about it [72]. Physical factors regulating CBPs depicted in Figure 2A can also include the amount of sunlight as it determines the release of hypothalamic orexins and so behavioural arousal [23], diets ( [43][44][45]) and the use of common psychostimulants (alcohol, tobacco) .…”
Section: Jingle-jangle Fallacies Related To Concepts Of "Environments"mentioning
confidence: 99%